The Good Indian's Guide to Queue-Jumping - V.Raghunathan (HarperCollins Publishers India, 2016)
A wise man once said that half of life is showing up -- and the other half is waiting in line. In a nation of a billion people, there's no escaping queues. We find ourselves in one every day -- whether to board a flight, for a darshan at Tirupati or, if we are less fortunate, to fetch water from municipal taps. We no longer wait for years for a Fiat car or a rotary-dial phone, but there are still queues that may last days, like those for school admissions. And then there are the virtual ones at call centres in which there's no knowing when we will make contact with a human. So if you can't escape 'em, can you beat 'em? Mercifully, yes. (After all, our national hero once pronounced, 'Hum jahan khade ho jaate hain, line wahin se shuru hoti hai,' and we made it our motto.) And if so, how can you jump queues better? Which excuse works like a charm? How should you backtrack if someone objects? Does it help to make eye contact? Are we generally accommodating of queue-jumpers and why? More importantly, what does queue-jumping say about us as a people? Does it mean we lack a sense of fairness and basic concern for others? These are questions of everyday survival that bestselling author V. Raghunathan first threw up in Games Indians Play and now takes up at length in The Good Indian's Guide to Queue-jumping.